Education Policy in Indonesia Year 2020-2024 - Setiawan, Nuri Rizki (Universitas Negeri Malang, 2024)
Education is a very fundamental and complex sector of life. Education in its journey requires a direction and a map that leads to the goals and ideals of a country. In the educational journey, a binding policy is needed so that the educational journey process can be carried out in a systematic and directed manner. Educational policies that are right on target are a necessity to encourage the realization of educational ideals themselves. This article will discuss the various education policies implemented in 2020- 2024. This aims to be able to describe and analyze various educational policies and their implementation in the field. The research method used is the library method (library research) by exploring various relevant research both from books and journals. The presentation of this article uses a qualitative method with a descriptive approach based on the writings of educational experts, trying to map the educational policies that have been implemented. The research results show that there are 5 central policies taken during the 2020-2024 period, namely 1) Increasing the distribution of quality education services, 2) Increasing productivity and competitiveness, 3) Mental revolution and fostering the Pancasila ideology, 4) Mental revolution and fostering the Pancasila ideology, 5) Increasing literacy, innovation and creativity.